Real-time monitoring of the associations between self-critical and self-punishment cognitions and nonsuicidal self-injury. (February 2021) - Burke, Taylor A.; Fox, Kathryn; Kautz, Marin; Siegel, David M.; Kleiman, Evan; Alloy, Lauren B.
Abstract: The Defective Self Model of nonsuicidal self-injury (NSSI) proposes that some people engage in NSSI to punish themselves and/or to respond to self-critical cognitions. Although there is a growing body of research to support this theory, there has been a lack of ecologically valid approaches employed to critically examine its tenets. The current study aimed to fill this gap in the literature. A sample of 64 undergraduates with a history of repetitive NSSI were recruited and completed an ecological momentary assessment (EMA) protocol. At baseline, participants completed trait measures of self-criticism and self-punishment cognitions. Over the EMA period, participants reported their experience of self-critical and self-punitive cognitions, and NSSI urge intensity three times daily. Our between-persons level findings suggest that trait and aggregated state self-punishment, but not self-critical cognitions, predict NSSI urges experienced over the EMA period. Our findings additionally provide evidence that both momentary self-critical and self-punishment cognitions are concomitantly and prospectively associated with NSSI urge intensity as measured in real-time and modeled at a within-persons level. However, after adjusting for concurrent NSSI urge intensity in prospective models, these within-persons level findings do not hold. Nevertheless, our findings provide greater support for the Defective Self Model of NSSI. Highlights: We assessed momentary self-criticism (SC), self-punishment (SP) and NSSI using EMA. Trait SP predicted NSSI urges over the EMA period. Momentary SC and SP were concomitantly associated with NSSI urge intensity. Momentary SC and SP were prospectively associated with NSSI urge intensity. Within-persons prospective relations did not hold adjusting for prior alert NSSI urge.